Perintisan Gereja Sebagai Bagian Dari Implementasi Amanat Agung - Simon Simon; Semuel Ruddy Angkouw (Manna Rafflesia, 2021)
This paper discusses the initiation of the church as part of the implementation of the Great Commission. The method used in this paper is a qualitative method with a literature approach. Planting churches is part of the Great Commission because the pioneers of the church implement the spread of the Gospel to the established congregations. If we trace the PB (New Agreement) and its historical records in determining the pioneering locations of the church, God and man played a role. From God's point of view, it is theological basis when Paul and Silas prayed, then the Holy Spirit gave instructions on where they should go (Acts 16: 4-12). While from humans, the apostles sent people to preach the Gospel in the designated areas. In this pioneering exercise in identifying culture, it requires the involvement of mentoring involved. In starting a new church planting, focus on the arrangement of faith to new converts as well as on the congregation that will join as members but take priority over discussing material matters.